Students' Mathematical Problem-Solving Process on Minimum Competency Assessment Test in the Context of Local Wisdom (Universitas Pendidikan Indonesia Kampus Cibiru, 2023)
The ability of students to solve AKM problems is an important thing for teachers to know in teaching. Because the AKM framework is in line with the PISA framework, this study aims to see how the process is carried out by students in solving AKM problems within the local cultural context. Research is a qualitative study with a hermeneutic phenomenological approach. The analysis of 7 junior high school students selected by purposive sampling resulted in findings in the form of the stages of solving AKM problems carried out by students who did not fully use the Polya stage. However, the initial stage follows what Polya said: understanding the problem. When referring to Polya's four steps, the second to fourth steps are performed simultaneously, not standing alone. Students solving skills are important to continue to develop as capital for their future sustainability. Practising problem-solving skills can be done in many ways, including using the stages offered by researchers such as the Polya, Bransford, Good and Brophy, Hohn and Frey, Ormrod, and Sternberg stages.